ANALISIS PENGAKUAN PENDAPATAN JASA IKLAN BERDASARKAN PSAK NO. 34 PADA PERUSAHAAN MEDIA CETAK PT. MEDIA BENGKULU EKSPRESS - Melta Afrianti; Furqonti Ranidiah (Yayasan Insani Mandiri Santani, 2025)
This research aims to determine the recognition of advertising services income based on PSAK No.34 at the print media company PT Media Bengkulu Ekspress. This research uses data collection techniques through observation, interviews and documentation. The subjects in this research were 4 people consisting of the General Manager, Advertising, Marketing Manager and Finance Admin. The research method used is descriptive qualitative in recognizing advertising services revenue based on PSAK NO.34, 4 methods namely Percentage of Completion, Completed Contract method, Revenue Recognition and Revenue Recognition at the Time of Payment. The results of this research indicate that PT Media Bengkulu Ekspress has complied with PSAK No. 34 to recognize revenue in advertising services by increasing relationships and approaching consumers, then submitting a cooperation proposal to obtain a cooperation contract agreement, after the contract has been agreed, the advertisement will aired and advertisements that have been recapped in accordance with the initial agreement will be billed to obtain final results which will be considered income. Keywords: Revenue Recognition